(untitled) (TAJ: Journal of Teachers Association, 2018)
Objectives : To determine the prevalence, aetiology and susceptibility profile of bacterial agents of wound infection among in- and- out patients. Methods : Wound swabs collected from 150 patients were, cultured and microbial isolates identified using standard methods. Antibiotic susceptibility testing was done on bacterial isolates. Results : Of the 150 swabs 131 (87.4%) were culture positive for bacterial pathogens, while 19 (12.6%) were bacteriologically sterile showing an isolation rate of 87.4%. The predominant bacteria isolated from the infected wounds were Staphylococcus aureus 47 (32.4%) followed by Escherichia coli 29 (20%), Proteus species 23 (16%), Coagulase negative Staphylococci 21 (14.5%), Klebsiella pneumoniae 14 (10%) and Pseudomonas aeruginosa 11 (8%). All isolates showed high frequency of resistance to ampicillin, penicillin, cephalothin and tetracycline. The flouroquinolones were the most potent antimicrobial agents against bacterial isolates from both in - and out -patients. Conclusion : Staphylococcus aureus was the most predominant etiologic agent of wound infection among in and out patients. A generally higher resistance pattern was observed among nosocomial bacterial pathogens. Prudent use of antibiotics is recommended. TAJ 2011; 24(2): 136-141